2019
DOI: 10.18203/2349-3291.ijcp20193742
|View full text |Cite
|
Sign up to set email alerts
|

Outcome analysis of a newly setup pediatric intensive care unit in a teaching hospital of northern India

Abstract: Background: Pediatric intensive care units (PICU) have brought about dramatic increase in the survival of critically ill children. The aim of pediatric intensive care is not just to save lives but also to maximise the quality of those lives. Evaluation of the outcome of an intensive care unit is necessary as a measure of quality improvement in patient care.Methods: A retrospective observational study was done in a PICU of a teaching hospital between February 2017 to August 2018. Records of all admissions, tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…In this study, the maority of pediatrics admitted were aged between 2-year and 5-years. This is inline with study conducted in India which stated that more than 36% patients were between 1 and 5 year, and about 32% were infants [14]. Similar study conducted in Nigeria showed different from our study.…”
Section: Discussionsupporting
confidence: 52%
“…In this study, the maority of pediatrics admitted were aged between 2-year and 5-years. This is inline with study conducted in India which stated that more than 36% patients were between 1 and 5 year, and about 32% were infants [14]. Similar study conducted in Nigeria showed different from our study.…”
Section: Discussionsupporting
confidence: 52%
“…The main factor related to DAMA, in our study, was primarily financial and is consistent with prior studies conducted in developing countries such as India where DAMA ranges from 3 to 25.9%. 15,16 Additional factors such as domestic problems and poor prognosis further contribute to the presence of DAMA. 17,18 In our study, the most common cause of ARDS was pulmonary due to bronchopneumonia.…”
Section: Discussionmentioning
confidence: 99%